C-reactive protein as a biomarker for immune-related adverse events in melanoma patients treated with immune checkpoint inhibitors in the adjuvant setting. Issue 4 (August 2021) - Lauwyck, Justine; Beckwée, Aline; Santens, Arno; Schwarze, Julia Katharina; Awada, Gil; Vandersleyen, Valérie; Aspeslagh, Sandrine; Neyns, Bart
Abstract : The objective of this study was to evaluate the utility of serum C-reactive protein (CRP) as biomarker for the early diagnosis of immune-related adverse events (irAEs) in melanoma patients treated with immune checkpoint inhibitors (ICIs) in the adjuvant setting, and its potential correlation with relapse-free survival (RFS). Prospectively collected data from 72 melanoma patients treated with adjuvant ICIs were pooled. CRP values at diagnosis of 10 irAEs were descriptively analysed. Correlations between RFS and the occurrence of irAEs, the grade of the irAE, the extent of CRP-elevation and the use of corticosteroids for irAE treatment were investigated. A total of 191 irAEs (grade 1/2, n  = 182; grade 3/4, n  = 9) occurred in 64 patients [skin toxicity ( n  = 70), fatigue ( n  = 50), thyroiditis ( n  = 12), musculoskeletal toxicity ( n  = 11), sicca syndrome ( n  = 10), other ( n  = 23), pneumonitis ( n  = 6), colitis ( n  = 4), hepatitis ( n  = 3) and hypophysitis ( n  = 2)]. In pneumonitis and hypophysitis, the median CRP levels at diagnosis exceeded the upper limit of normal (ULN, 5 mg/L). After a median follow-up of 26.5 months, 28 patients (39%) had been diagnosed with a melanoma relapse. Patients who experienced no irAE were at the highest risk for relapse ( P  = 0.008). A trend was observed for patients diagnosed with an irAE that was associated with an elevated CRP (>2xULN) to be at higher risk for relapse as compared to those diagnosed with an irAE and CRP <ULN ( P  = 0.054). CRP has potential as biomarker for the early detection of selected irAEs. Dynamic evaluation can guide irAE diagnosis, regression or relapse. The observed correlation between irAEs associated with an elevated CRP and risk for recurrence deserves further investigation.